Isokinetic hamstring and quadriceps muscle strength profiles of elite South African football players - Aginsky, J. D.; Neophytou, N.; Charalambous, T. (African Journal for Physical, Health Education, Recreation and Dance, 2014)
Football players are at risk of lower limb injuries, specifically hamstring muscle strains and ACL injuries due to muscle imbalances. This was a descriptive study assessing the isokinetic hamstring and quadriceps muscle strength and endurance in 28 elite, male, South African football players. Muscle strength was tested at 60./s over 5 repetitions concentrically and eccentrically. Muscle endurance was tested at 180./s over 15 repetitions. Peak torque to body weight ratio (PT/BW); reciprocal ratio (H/Q); dynamic control ratio (DCR), bilateral ratio and relative fatigue were calculated. Data were analyzed using a Levenees t-test. The concentric H/Q ratios (Dominant: 64.7± 9.3% and Non-dominant: 60.9 ± 11.1%) and eccentric ratios (Dominant: 69.0 ± 12.2% and Non-dominant: 67.0 ± 12.8%) at 60o/s were within normal range. The DCR showed slight eccentric hamstring weakness (Dominant: 0.85 ± 0.14 and Non-dominant: 0.83 ± 0.20). The PT/BW ratio showed stronger concentric hamstring strength and endurance on the dominant side compared to the Non-dominant side (Dominant: 60o/s: 204.6 ± 24.3% and 180 o/s: 158.8 ± 21.1% vs. Non-dominant: 60o/s: 198.4 ± 49.6% and 180 o/s: 146.4 ± 18.7%). The hamstring muscles (Dominant: 30.0 ± 8.8% and Non-dominant: 29.0 ± 13.0%) were less fatigue resistant compared to the quadriceps muscles (Dominant: 23 ± 6.4% and Non-dominant: 20.7 ± 7.8%). The study concluded that South African (SA) football players present with eccentric weakness and less fatigue resistance in the hamstring muscles, which together may predispose them to hamstring muscle strains.